2017
DOI: 10.1371/journal.pone.0173369
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity, feeding selectivity, and responses to fruit scarcity of two sympatric Bornean primates (Hylobates albibarbis and Presbytis rubicunda rubida)

Abstract: Effectively characterizing primate diets is fundamental to understanding primate behavior, ecology and morphology. Examining temporal variation in a species’ diet, as well as comparing the responses of different species to variation in resource availability, can enhance understanding of the evolution of morphology and socioecology. In this study, we use feeding data collected over five years to describe the diets of two sympatric Southeast Asian primate species of similar body size: white-bearded gibbons (Hylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…However, despite the increase in feeding time, there was no commensurate increase in food intake, presumably because the fibre‐rich foods that were eaten in greater amounts were eaten more slowly (Oftedal, ). The foraging strategy employed by female chimpanzees during fig‐months was thus typical of frugivorous primates during fruit‐scarce periods, involving changes both in diet composition and in time spent feeding (Clink et al, ; Conklin‐Brittain et al, ; Doran, ; Felton et al, ; Irwin et al, ; Tutin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the increase in feeding time, there was no commensurate increase in food intake, presumably because the fibre‐rich foods that were eaten in greater amounts were eaten more slowly (Oftedal, ). The foraging strategy employed by female chimpanzees during fig‐months was thus typical of frugivorous primates during fruit‐scarce periods, involving changes both in diet composition and in time spent feeding (Clink et al, ; Conklin‐Brittain et al, ; Doran, ; Felton et al, ; Irwin et al, ; Tutin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this lower quality, figs are major fallback foods because they are abundant and available year‐round, allowing the proportion of figs in the diet to increase when drupes are scarce (Marshall & Wrangham, ; Wrangham et al, , ). Hence, it has been reported that Kanyawara chimpanzees, such as gibbons ( Hylobates albibarbis ), spider monkeys ( Ateles chamek ) and orangutans, prefer drupes when they are available (Clink, Dillis, Feilen, Beaudrot, & Marshall, ; Felton et al, ; Leighton, ; Wrangham et al, ). The previous studies of Kanyawara chimpanzees revealed that during drupe‐months, there were increased intake of nonstructural carbohydrates and reduced intake of fibre (Conklin‐Brittain, Wrangham, & Hunt, ; Wrangham, Conklin‐Brittain, & Hunt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Primates display a wide array of dietary and behavioral adaptations to maintain adequate nutrient intake and balanced energy during periods of food scarcity (Clink, Dillis, Feilen, Beaudrot, & Marshall, ; Doran, ; Knott, ; Mitani & Watts, ; Remis, Dierenfeld, Mowry, & Carroll, ; Serckx et al, ). Chimpanzees ( Pan troglodytes ) primarily occupy tropical forests characterized by high rainfall (>1800 mm annually), but they are ecologically flexible and also use habitats such as savannah woodland and seasonally dry montane forests (Basabose, ; Gross‐Camp & Kaplin, ; Isabirye‐Basuta, ; Kano, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although fallback food data is unknown for H. l. entelloides and H. l. carpenter , data on fallback foods is available for another Hylobates species. Hylobates albibarbis is known to eat foods that require increased postcanine masticatory loads, such as leaves and unripe fruit, during periods of fruit scarcity (Clink, Dillis, Feilen, Beaudrot, & Marshall, 2017; Vogel, Haag, Mitra‐Setia, van Schaik, & Dominy, 2009). Therefore, it is possible that relative to insular hylobatids, mainland taxa experience selective pressure for mastication of tougher and/or stiffer foods.…”
Section: Discussionmentioning
confidence: 99%